MASTERING EFFECTIVE BUSINESS COMMUNICATION WRITING SKILLS BY FUTURE INTERNATIONAL RELATIONS PROFESSIONALS - Василишина, Н. M. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2014)
The article under consideration is related to the problem of mastering writing skills by future international relations professionals. The problem is that for the last ten years its performance has declined in comparison with other foreign сommunication skills at all key stages. In our investigation, the history of teaching-of-writing approaches over the last 50 years was characterised by five phases, some elements of which have been and continue to be concurrent in the best practice. Modern review has differentiated six types of every-day writing, important in real life business intercourse: personal writing, public writing, creative writing, social writing, study writing, institutional writing. From a pedagogical point of view, techniques for improving writing will include practice in writing by the very teachers who are teaching it. Dialogic teaching is identified as an important element in improving the quality of interaction and thought on the part of students in the class. Also various types of barriers to effective writing communication were cosidered as a first step in improving communication style in future international relations professionals. Empirical teaching methods as well as creative context were outlined in the survey